USAHATANI INTEGRASI PADI HITAM & LELE SANGKURIANG DENGAN SISTEM AKUAPONIK (Studi Kasus Di Kelompok Tani Terpadu Angsana Kelurahan Pengasinan, Kecamatan Sawangan, Kota Depok, Jawa Barat) - Alvin Putra Priyambodo; M. Gunardi Judawinata (Universitas Galuh, 2023)
Every year, Depok City always experience a decrease in their agricultural area but in 2020, a community form an integrated farmer group named Angsana Integrated Farmer Group in the middle of a residential area. This farmer group utilize a public facility land that has been neglected by building black rice and sangkuriang lele farming with an aquaponic system. The aim of this study is to obtain the characteristic of the Angsana Integrated Farmer Group and to find out the feasibility aspect of the black rice and sangkuriang lele farming business with the aquaponic system. Data collection techniques were carried out in library research, interviews, observation and documentation. This feasibility study is observed descriptively from non-financial aspects such as legal, market and marketing, environmental, management, human resources, technical, technological, and financial aspects. The results of this research showed that the aquaponic business is feasible to run from the non-financial aspect by taking notice of the needs of every aspect. Financial analysis of the black rice and sangkuriang catfish farming after calculating using financial feasibility criteria also showed that this business is feasible to run.